Dampak Penggunaan Media Sosial terhadap Interaksi dalam Hubungan Keluarga: Studi Kasus pada Remaja dan Orangtua di Kabupaten Aceh Selatan - Fazlullah, Bazkara; Abd Madjid; Fatimahsyam (Journal of Practice Learning and Educational Development, 2026)
This research aims to analyze the impact of social media usage on interactions within family relationships between teenagers and parents in South Aceh Regency. The research uses a qualitative approach with a case study method conducted in Gampong Gunung Ketek, Samadua District. Data were obtained thru in-depth interviews, observations, and documentation from ten informants consisting of five teenagers and five parents. The research results show that the use of social media has an ambivalent effect on family relationships. WhatsApp and YouTube have a positive impact because they can strengthen communication, facilitate the exchange of information, and create moments of family togetherness. On the other hand, TikTok and Instagram tend to reduce the intensity of face-to-face interactions, foster individualism, and widen the communication gap between generations. Facebook, although increasingly less used by teenagers, still serves as a medium for maintaining relationships among parents and extended family. In general, this research emphasizes that the influence of social media on family relationships highly depends on the intensity of use, the purpose of interaction, and the values upheld within the family. Therefore, digital literacy and proportional supervision are necessary so that social media can be utilized as a means to strengthen, not weaken, family harmony in the digital era.